ANALISIS STRATEGI PEMASARAN PADA PABRIK ROTI “SELEB BAKERY” DI KUALASIMPANG - Rahmi Meutia (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2019)
This study aims to find out the most appropriate marketing strategy to be applied for Seleb Bakery Bread Factory at Kuala Simpang and to find out the factors that become strengths, weaknesses, opportunities and threats. Data is collected by observation and direct interview. The data was analyzed by SWOT Matrix Analysis, namely the internal environmental analysis of IFAS (Internal Strategic Factors Analysis Summary) and external environmental analysis of EFAS (External Strategic Factors Analysis Summary) with a descriptive qualitative approach, then using IFAS-EFAS matrix.Based on the results of internal matrix analysis with a value of 2.54 and external matrix with a value of 2.67, the Seleb Bakery Bread Factory in Kuala Simpang is in a moderate position. And the IFAS-EFAS matrix is in column 5 which means that the Seleb Bakery Bread Factory in Kuala Simpang is still in growth or in diversification efforts. Based on the results of the analysis of the strategy determination on the Seleb Bakery bread factory in Kualasimpang are: (1) S-O Strategy that is to maintain price and product quality to increase the satisfaction and loyalty of costumer and to utilize strategic factory location to establish cooperation with distributor agents in expanding the marketing area. (2) W-O Strategy that is technology based promotion and open the bakery stores in strategic place, (3) S-T Strategy that is maintain the quality and price of products so that the customer do not buy similar products or switch to substitute products and improve product quality in accordance with the pattern of costumer interest and (4) W-T Strategy that is to improve the quality of human resources by giving trainings to recruit more skilled employees. Marketing strategy, analysis of IFAS, Bakery stores